Decoupling Actions from Consequences: Dorsal Hippocampal Lesions Facilitate Instrumental Performance, but Impair Behavioral Flexibility in Rats - Busse, Sebastian; Schwarting, Rainer K. W. (Frontiers in Behavioral Neuroscience, 2016)
The present study is part of a series of experiments, where we analyze why and how damage of the rat’s dorsal hippocampus can enhance performance in a sequential reaction time task. In this task, sequences of distinct visual stimulus presentations are food-rewarded in a fixed-ratio-13-schedule. Our previous study (Busse and Schwarting 2016) had shown that rats with lesions of the dorsal hippocampus show substantially shorter session times and post-reinforcement pauses than controls, which allows for more practice when daily training is kept constant. Since sequential behavior is based on instrumental performance, a sequential benefit might be secondary to that. In order to test this hypothesis in the present study, we performed two experiments, where pseudorandom rather than sequential stimulus presentation was used in rats with excitotoxic dorsal hippocampal lesions. Again, we found enhanced performance in the lesion-group in terms of shorter session times and post-reinforcement pauses. During the sessions we found that the lesion-group spent less time with non-instrumental behavior (i.e. grooming, sniffing, and rearing) after prolonged instrumental training. Also, such rats showed moderate evidence for an extinction impairment under devalued food reward conditions and significant deficits in a response-outcome-discrimination task in comparison to a control-group. These findings suggest that facilitatory effects on instrumental performance after dorsal hippocampal lesions may be primarily a result of complex behavioral changes, i.e. reductions of behavioral flexibility and/or alterations in motivation, which then result in enhanced instrumental learning.